Improvement of thermal efficiency in cement mortars by using synthetic feldspars. (1st February 2021) - Torres-Carrasco, M.; Enríquez, E.; Terrón-Menoyo, L.; Cabrera, M.J.; Muñoz, D.; Fernández, J.F.
Highlights: Reuse of feldspar in construction materials. Functional properties are highly improved with the replacement of sand by feldspar. Heat-islands in cities could be reduce using these materials. Abstract: The use of white cements as a building material is widely employed due to its high whiteness and reflectance. However, building materials should adopt better thermal insulation characteristics to contribute for a significant urban heat-islands mitigation. In this work, synthetic feldspar has been evaluated as partial and total replacement of sand in white cement mortars. Thermal, mechanical, and optical properties of these new mortars are characterized by thermal conductivity, compression resistance test and reflectance-colorimetry, respectively. The replacement of sand by synthetic feldspar allows to obtain white mortars having ≈18% improvement in solar reflectance. Experiment under solar irradiance of mortars having synthetic feldspars reduce the surface heating of the mortar in 25% and the heating transmission to the rear of the mortar in >55%. Moreover, the high crystallinity of the synthetic feldspar reduces the mortar expansion due alkali-silica reactions (ASR). Improvement in reflectance and thermal conductivity resistance of white cement mortar having synthetic feldspar opens a wide range of building material applications.